Time lags in the pass-through of crude-oil prices: Big data evidence from the German gasoline market - Frondel, Manuel; Vance, Colin; Kihm, Alex (Technische Universität Dortmund, 2015)
This note investigates the pass-through of global Brent oil notations to fuel prices across the oligopoly of retail majors in Germany. We assemble a high-frequency panel data set that encompasses millions of price observations and allows us to distinguish effects by brand. Upon establishing a cointegrating relationship between fuel and crude-oil prices using daily data, we estimate an error-correction model (ECM) and find that (1) the pass-through of oil prices critically depends on the number of time lags included in the ECM, (2) strict adherence to classical information criteria for determining lag length yields extremely long pass-through durations, and (3) the estimated impulse response functions are virtually identical across brands, irrespective of the lag count, suggesting a high degree of competition among brands.
Discussion Paper / SFB 823;24/2015
Keywords: retail markets; error-correction model; competition; 310; 330; 620